Grammatical Errors in the English Translation Made by the Students of English Study Program of UKI Toraja - Matius Tandikombong; Haryanto Atmowardoyo (Universitas Negeri Makassar, 2016)
This research is aimed at describing the grammatical errors made by the students in translating Indonesian into English. Four objectives are fromulated: 1.To find out the types of errors that the students make in translating sentences from Indonesian into English 2.To find out the most frequent errors made by the students of UKI Toraja 3.To find out the source of error that the students make in translating Indonesian text into English text and 4. To find out the differences in number of grammatical errors made the students of different levels of UKI Toraja. The method used was a descriptive method. The population of this research was the fourth-semester and the sixth-semester students of UKI Toraja in the academic year 2014/2015. The fourth-semester students consisted of 270 as the population in this research. Thirty (30) students were taken as the sample. The sixth-semester students also consisted of 270 students as a population in this research and30 students were taken as the sample. The research findings reveal that the most frequent errors in both levels are errors in verbs; and that most of the errors are due to overgeneralization and the ignorance of the rule restriction. Keywords: Grammatical errors, Indonesian text, English text, Verb, Noun, Conjunction, Pronoun, Adjective, Adverb, Article, Preposition.